High-Frequency Electromagnetic Field Coupling to Small Antennae in a Rectangular Resonator - Sergey Tkachenko; Jürgen Nitsch; Moawia Al-Hamid (International Journal of Antennas and Propagation)
The integral-differential equation for the current of an electrically small antenna, inside a resonator, which is induced by given sources, is approximately solved by the so-called “Method of Small Antenna,” both for dipole and loop antennas. The current induced in the antenna is evaluated using the scattering characteristics of small antennas in free space and regularized Green’s function of resonator. As example of application of the theory, a transfer function (“external field→induced voltage”) for the coupling through aperture is calculated.